Thermal analysis of 99.4% pure aluminium granules during investment casting by in-situ melting technique - Saleh, Aslinda (Penerbit UTHM, 2020)
Investment casting is a precision casting used for producing complex or near-net shape products such as industrial parts, aerospace, automotive and defence components (Adrian, Andreas, Carol, & Vasile, 2013; Vaezi, Safaeian, & Chua, 2011; Yadav & Karunakar, 2011). The investment casting process is further developing in conjunction with current technology including computer aided design and additive manufacturing that able to produce medical implants (Horáček et al., 2011; Kumar, Ahuja, & Singh, 2016; R. Singh & Singh, 2014). Nevertheless, the parameters involved in the investment casting process influencing the quality of the product also known as castings. Parameters such as the ceramic mould preheat temperature, pouring temperature and hydrogen content contribute to porosity problem in the castings. Careful control of the process parameters able to improve the porosity issue by lowering the ceramic mould preheat temperature and pouring temperature with low hydrogen content (Li & Li, (2001). In addition the low ceramic mould preheat and pouring temperature increasing the mechanical properties of the castings (Yadav & Karunakar, 2011).